2015
DOI: 10.1126/science.aaa9816
|View full text |Cite
|
Sign up to set email alerts
|

The landing(s) of Philae and inferences about comet surface mechanical properties

Abstract: The Philae lander, part of the Rosetta mission to investigate comet 67P/Churyumov-Gerasimenko, was delivered to the cometary surface in November 2014. Here we report the precise circumstances of the multiple landings of Philae, including the bouncing trajectory and rebound parameters, based on engineering data in conjunction with operational instrument data. These data also provide information on the mechanical properties (strength and layering) of the comet surface. The first touchdown site, Agilkia, appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
142
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 232 publications
(152 citation statements)
references
References 21 publications
9
142
0
1
Order By: Relevance
“…Philae first touched down at 15:34 UT at the selected Agilkia "J" landing site on the head of the nucleus of 67P, where it failed to anchor at the surface. Then, it bounced three times for an additional two-hour flight (Biele et al 2015) before finally landing at a site later named Abydos, about 1 km away from the first touchdown. During the lander descent the comparison between high-resolution images acquired by the ROsetta Lander Imaging System (ROLIS) onboard Philae (Mottola et al 2007(Mottola et al , 2015 with those obtained by the Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS, Keller et al 2007) allowed the identification of the first touchdown point.…”
Section: Introductionmentioning
confidence: 99%
“…Philae first touched down at 15:34 UT at the selected Agilkia "J" landing site on the head of the nucleus of 67P, where it failed to anchor at the surface. Then, it bounced three times for an additional two-hour flight (Biele et al 2015) before finally landing at a site later named Abydos, about 1 km away from the first touchdown. During the lander descent the comparison between high-resolution images acquired by the ROsetta Lander Imaging System (ROLIS) onboard Philae (Mottola et al 2007(Mottola et al , 2015 with those obtained by the Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS, Keller et al 2007) allowed the identification of the first touchdown point.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, data from the Surface Electrical Sounding and Acoustic Monitoring Experiment (SESAME) on Philae and Philae's landing gear indicated that Agilkia apparently has a soft and granular surface (∼ 20 cm in thickness) on top of a more rigid, icy subsurface . In contrast, Abydos was found to consist mostly of rigid, icy material (Biele et al 2015;Spohn et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…On 12 November, when Philae impacted on the solarilluminated Agilkia, it excavated ∼ 0.4 m 3 of regolith from 67P's top surface layer (Biele et al 2015). De Sanctis et al (2015) discussed in detail a temperature gradient that exists between the top layer of the surface, which is reported to have a temperature between about 180 K and 230 K during daytime whereas the temperature of the subsurface, at a depth of 4 cm is, even during daytime, only about 130 K. Therefore, we infer that Philae's excavation would have suddenly exposed the colder subsurface to the higher temperatures of the solar insolated surface and that this process would have rapidly caused the sublimation of volatile species from dust grains present in the subsurface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations